2005
DOI: 10.1080/09553000500103082
|View full text |Cite
|
Sign up to set email alerts
|

Translocation yields in peripheral blood lymphocytes from control populations

Abstract: For retrospective biological dosimetry purposes a generic age-dependent control level can be assumed. No other lifestyle factors such as smoking appear to have a significant effect on translocation yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
6

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 11 publications
4
28
1
6
Order By: Relevance
“…De nombreuses publications attestent que le taux de translocations augmente significativement avec l'âge (Darroudi, 2000 ;Edwards et al, 2005 ;Pressl et al, 1999 ;Ramsey et al, 1995 ;Sigurdson et al, 2008 ;Sorokine-Durm et al, 2000a ;Whitehouse et al, 2005). Ces études peuvent être regroupées en deux groupes : celles regroupant les données issues de plusieurs laboratoires pour avoir plus de poids statistique (Sigurdson et al, 2008 ;Sorokine-Durm et al, 2000b ;Whitehouse et al, 2005), et celles qui présentent les données d'un seul laboratoire (Darroudi et Natarajan, 2000 ;Pressl et al, 1999 ;Ramsey et al, 1995) (Tab.…”
Section: Effet De L'âgeunclassified
See 2 more Smart Citations
“…De nombreuses publications attestent que le taux de translocations augmente significativement avec l'âge (Darroudi, 2000 ;Edwards et al, 2005 ;Pressl et al, 1999 ;Ramsey et al, 1995 ;Sigurdson et al, 2008 ;Sorokine-Durm et al, 2000a ;Whitehouse et al, 2005). Ces études peuvent être regroupées en deux groupes : celles regroupant les données issues de plusieurs laboratoires pour avoir plus de poids statistique (Sigurdson et al, 2008 ;Sorokine-Durm et al, 2000b ;Whitehouse et al, 2005), et celles qui présentent les données d'un seul laboratoire (Darroudi et Natarajan, 2000 ;Pressl et al, 1999 ;Ramsey et al, 1995) (Tab.…”
Section: Effet De L'âgeunclassified
“…Ces études peuvent être regroupées en deux groupes : celles regroupant les données issues de plusieurs laboratoires pour avoir plus de poids statistique (Sigurdson et al, 2008 ;Sorokine-Durm et al, 2000b ;Whitehouse et al, 2005), et celles qui présentent les données d'un seul laboratoire (Darroudi et Natarajan, 2000 ;Pressl et al, 1999 ;Ramsey et al, 1995) (Tab. II).…”
Section: Effet De L'âgeunclassified
See 1 more Smart Citation
“…The calculation of the biological radiation doses on the frequency of reciprocal translocations using 3-4 chromosomes (representing approximately 20% of the genome) showed that FISH technique can be used for retrospective group dosimetry for the doses above 25 cGy (one should score 1000 cells, genome equivalent) and for the individual dosimetry 2000 cells genome equivalent is recommended. For situation of exposure in dose range ~ 30 -200 cGy, 1000, and 500 cells genome equivalent, respectively should be sufficient, taking into account the factor of aging [18,20,21]. In order to reduce number of cells for analysis and to detect all structural as well as numerical aberrations simultaneously in one preparations a multi-colour FISH technique is developed and applied for whole genome analysis of human chromosomes using 23/24 different colours for 23/24 different human chromosomes [26].…”
Section: Post Chernobyl Experiences (In Human Studies)mentioning
confidence: 99%
“…Among these assays the control level (unexposed samples) of chromosomal alterations is in order of: micronuclei (3-35) > translocations (0-15) > dicentrics (1-4) > PCC (0-2) per 1000 cells analyzed [6]. For both MN and translocation assays influence of age on increasing level of chromosomal alterations was evident [6,20,21]. Moreover, smoking status suggests an acceleration of translocation ≥ age of 60 years old [21].…”
Section: Frequency Of Spontaneously Occurring Chromosomal Alterationsmentioning
confidence: 99%